2018
DOI: 10.1007/s10257-018-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding user behavior of virtual personal assistant devices

Abstract: With the development of artificial intelligence technology, the market for virtual personal assistant (VPA) devices is emerging as a new battleground for global information technology companies. This study develops a comprehensive research model, based on perceived value theory, to explain potential customers' intentions to adopt and use VPA devices. It investigates the relationship between perceived usefulness, perceived enjoyment, and product-related characteristics (i.e., portability, automation, and visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 72 publications
5
104
0
3
Order By: Relevance
“…Therefore, by collecting and analyzing the personal music listening information from the users and providing them with curated playlists in return, helps in increasing the hedonic value of the VA devices. Existing research has also confirmed this benefit component of the enjoyment aspect in a number of other different contexts [56][57][58]. While the utilitarian aspect is fundamental to the adoption and use of any IT-related service, the enjoyment motivation to use those services is fundamental to the success of such services [60].…”
Section: The First Channel: Antecedents Of Perceived Benefitsmentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, by collecting and analyzing the personal music listening information from the users and providing them with curated playlists in return, helps in increasing the hedonic value of the VA devices. Existing research has also confirmed this benefit component of the enjoyment aspect in a number of other different contexts [56][57][58]. While the utilitarian aspect is fundamental to the adoption and use of any IT-related service, the enjoyment motivation to use those services is fundamental to the success of such services [60].…”
Section: The First Channel: Antecedents Of Perceived Benefitsmentioning
confidence: 80%
“…Perceived enjoyment captures the feelings and emotions of the users such as joy or pleasure that using a product or service generates [56]. Users who experience pleasure and joy from using a technology or service (apart from their instrumental value) tend to adopt those and use them more extensively than others [56][57][58]. For example, using the services of the VA for playing music is one of the most frequently performed activity by the users [59].…”
Section: The First Channel: Antecedents Of Perceived Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and validity of the latent variables were verified before the hypothesis testing. The research model and hypothesis assessment were conducted using the partial least squares structural equation modeling (PLS-SEM) analytical technique, which maximizes predictive power while minimizing the prediction error between the latent and measured variables [60]. In addition, this technique allows researchers to conduct a meaningful analysis even when the sample size is relatively small (Henseler et al, 2016).…”
Section: Research Proceduresmentioning
confidence: 99%
“…For example, Fan et al (2018) [21] conducts the adoption of AI-based medical diagnosis through the combination of UTAUT and trust theory. Yang and Lee (2018) [63] attempts to explain the adoption of virtual personal assistant devices through perceived usefulness and perceived enjoyment. Akinnuwesi et al (2016) [5] explains biometric technology adoption through UTAUT.…”
Section: Literature Review and Theorymentioning
confidence: 99%